(3TQM GdSHY GdWhGds - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3GeQD GdbjS Hf MLQ Hf GdMGQK GdcfOj, ef Hfj Bcd GdeQGQs
(3ChdgG (B:s
(3bGd GdTjN GdJHQjRi QVi Gddg Yfg SCdJfi CMSf Gddg Jhajbc Cf CdNU dc TQM GdbUGFO GdSHY s
(3BNQgG (B:s
(3ef TQM eYdbI GdMGQK Hf MdRI eKdgG JNQL GdfUjMI ddbhe adGI ef OhfgG CadGA s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B351s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs